2022
DOI: 10.5937/jomb0-33999
|View full text |Cite
|
Sign up to set email alerts
|

Total anti-SARS-CoV-2 antibodies measured 6 months after Pfizer-BioNTech COVID-19 vaccination in healthcare workers

Abstract: Background: This study aimed at monitoring the kinetics of serum total anti-SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) antibodies in a cohort of healthcare workers after voluntary vaccination with Pfizer-BioNTech coronavirus disease 2019 (COVID-19).Methods: The study population consisted of 787 healthcare workers (mean age 44±12 years; 66% females), who received two 30 μg doses of Pfizer-BioNTech COVID-19 vaccine, 3 weeks apart. Venous blood was drawn before the first vaccine dose, immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…30 Studies looking into the relationship of age and humoral response after undergoing Pfizer-BioNTech vaccination noted an inverse relationship on the antibody titers mounted. 12,31 The studies included in Table 2 highlighted a similar trend.…”
Section: Contributing Factors To Declining Humoral Immunity Following Complete Mrna Vaccination Agementioning
confidence: 62%
See 3 more Smart Citations
“…30 Studies looking into the relationship of age and humoral response after undergoing Pfizer-BioNTech vaccination noted an inverse relationship on the antibody titers mounted. 12,31 The studies included in Table 2 highlighted a similar trend.…”
Section: Contributing Factors To Declining Humoral Immunity Following Complete Mrna Vaccination Agementioning
confidence: 62%
“…Ab titers of females were higher even after humoral decline in all studies (Table 3); however, the percentage decline from the peak was similar for both sexes (Figure 4). 12,25 While it is important to note that overall Ab titers may be influenced by the larger female population cohort (6,238 females vs. 3,128 males) involved in the included studies, this might be attributed to the sex-based difference in humoral immunity which affects vaccine responses. Previous studies indicated that females have a greater humoral response attributed to hormonal differences and X chromosomes leading to biallelic expression of certain genes.…”
Section: Sexmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Such vulnerability is correlated to the significant decline in anti‐SARS‐CoV‐2 antibodies (Abs) over time. 10 , 11 , 12 This waning humoral response could lead to breakthrough infections, thus highlighting the potential role of serologic testing to assess vaccine immunogenicity and protective efficacy. Although the role of T cells and B memory cells from vaccine‐induced immunity has yet to be fully elucidated, multiple studies showed that Ab levels directly correlate with the risk of vaccine reinfection and breakthrough, with low levels of anti‐SARS‐CoV‐2 immunoglobulin G (IgG) in patients with infections correlating with high viral load and duration of viral shedding.…”
Section: Introductionmentioning
confidence: 99%